Influence of the Use of IrrigationSolutionInhibitors in Improving Dentine Adhesion: A Systematic Review and Meta-Analysis - Pierre, Fernanda Z. [UNESP] (2024)
Introduction: This systematic review examined the effect of neutralizing agents on bond strength after irrigation with sodium hypochlorite and their existing protocols in literature. Methods: This present study adhered to the PRISMA guidelines and was registered at PROSPERO. Five electronic databases were searched (sept-2020/jan-2021) in English, Spanish, and Portuguese, without any restrictions on publication date. Cases reports, editorials and literature reviews were not included. The risk of bias was assessed using the Cochrane Collaboration tool. From the initial 7,147 studies, 2,745 were removed as duplicates and 4,382 were excluded after a title/abstract screen. Results: Seventeen in vitro studies were included. The results showed that the higher the concentration of sodium hypochlorite, the lower the bond strength at dentine/restoration interface (p<0.01). Among the studies, sodium ascorbate was the most widely used neutralizer and showed the most significant results in increasing bond strength (p<0.01). The bond strength values were found to increase with longer application time of the neutralizing substances (p<0.01). Conclusions: The use of sodium ascorbate as a neutralizing agent can reverse the negative effects of the sodium hypochlorite and improve the bond strength between dentine and resin cement, however, it isn’t possible to determine the best protocol for use.